2010
DOI: 10.1007/s00383-010-2703-5
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of the MYCN gene by siRNA delivered by folate receptor-targeted liposomes in LA-N-5 cells

Abstract: These results suggest that targeted delivery of MYCN siRNA by folate receptor-targeted lipid vesicles into LA-N-5 cells is efficacious and capable of suppressing MYCN mRNA expression both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In previous studies transferrin and insulin had successfully been attached to the activated HSA NP with Traut's reagent in order to react with the maleimide crosslinker NHS-PEG-MAL-5000 (Ulbrich et al, 2011). In the present study, folic acid was covalently linked to HSA NPs and NP uptake was studied in human neuroblastoma (UKF-NB-3) and rat glioblastoma (101/8) cells, representing two cell lines that can be targeted by the use of folic acid (Ciofani et al, 2008;Feng et al, 2010). Moreover, both cell lines are models for cancer diseases with a poor outcome.…”
Section: Introductionmentioning
confidence: 92%
“…In previous studies transferrin and insulin had successfully been attached to the activated HSA NP with Traut's reagent in order to react with the maleimide crosslinker NHS-PEG-MAL-5000 (Ulbrich et al, 2011). In the present study, folic acid was covalently linked to HSA NPs and NP uptake was studied in human neuroblastoma (UKF-NB-3) and rat glioblastoma (101/8) cells, representing two cell lines that can be targeted by the use of folic acid (Ciofani et al, 2008;Feng et al, 2010). Moreover, both cell lines are models for cancer diseases with a poor outcome.…”
Section: Introductionmentioning
confidence: 92%
“…For instance, folate-conjugated SNALPs (2.5% PEG, 2.5% folate-PEG) targeting folate receptors on cancer cells can knock down 40% of targeted MYCN gene in vivo [104]. AA-modified MCNPs (11% PEG, 11% AA-PEG) have three times gene silencing efficiency compared with non-modified LCPs [105].…”
Section: Surface Targeting Ligands On Sirna Deliverymentioning
confidence: 99%
“…showed that systemic administration of APRPG‐miR‐499 in mice bearing Colon 26 NL‐17 carcinoma significantly improved tumor blood flow, therefore, mice pre‐treated with APRPG‐miR‐499 exhibited enhanced tumor accumulation of DOX and, demonstrating superior anticancer effect of the combination therapy . Furthermore, the same strategy has been utilized by other groups to develop targeted cationic liposomes which proved remarkable in vitro and in vivo siRNA transfection efficiency; for example, FR‐targeted PCLs for MYCN siRNA delivery, and nucleolin‐targeted PCLs for anti‐BRAF siRNA delivery . Whitehead et al.…”
Section: Nanocarriersmentioning
confidence: 99%